Legal Determination of Husband's and Wife's Disobedience in Shia Law and the Islamic Law Compilation: A Comparative Study - Amirul Bakhri; Imam Taufiq (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Disobedience between husband and wife (nusyuz) in marriage remains a problem in contemporary Muslim society today. The theoretical argument developed so far is that there are different provisions regarding norms of disobedience between husband and wife in marriage in Islamic society. This research analyzes the problem of disobedience between husband and wife called nusyuz by comparing two different laws, namely the Islamic Law Compilation and the Shia Tafsir book by Nashir Makarim al-Syirazi, as the basis for Shia Law in Iran. The selection of these two laws is based on the argument that they have differences regarding the concept of nusyuz. The research method takes normative Islamic law. The approach uses a legal synchronization, conceptual, comparative, and historical approach. The research results show that the compilation of Islamic law only regulates the nusyuz of wives towards husbands, including punishment for wives, and not vice versa. Meanwhile, Shia law regulates the nusyuz carried out by both husband and wife, including punishment for each husband and wife who commits nusyuz. The basis of legal philosophy used in determining Shia law is equality of justice between humans in the law (murā'āt al-'adālah wa 'adamu tafrīq baina al-nās), as in the Shia Tafsir book by Nashir Makarim al-Syirazi. Therefore, it is necessary to reinterpret the nusyuz law to update Islamic law in the contemporary era.